Synthesis and characterization of tracers and development of a fluorescence polarization immunoassay for amantadine with high sensitivity in chicken. Issue 10 (21st September 2021) - Guo, Liuchuan; Liu, Meixuan; Li, Qiang; Dong, Baolei; Li, Hongfang; Mari, Ghulam Mujtaba; Liu, Rui; Yu, Wenbo; Yu, Xuezhi; Wang, Zhanhui; Zhang, Suxia; Shen, Jianzhong; et al.
Abstract : Abstract: Fluorescence polarization immunoassay (FPIA) is a homogeneous and rapid analytical method that is suitable for high‐throughput screening of large numbers of samples. However, FPIA typically suffers from lower sensitivity than the well‐established enzyme‐linked immunosorbent assay (ELISA), limiting its wide application as an analytical tool that can be run with trace levels of an analyte. Herein, a highly sensitive FPIA for detecting amantadine (AMD) in chicken is described. To achieve high sensitivity, nine chemical tracers of AMD that employ different fluoresceins, fluorescein derivatives, and haptens were synthesized and paired with four previously produced monoclonal antibodies (mAbs). The effect of the tracer structure on the sensitivity of FPIA was investigated and discussed. We found that the tracers with a linear and shorter bridge between adamantane and fluorescein generally provided higher sensitivity. After optimization, N′ ‐(1‐adamantyl) ethylenediamine (AEDA), an AMD structural analogue labeled with fluorescein isothiocyanate (FITC), achieved the lowest IC50 value (1.0 ng/ml) in the FPIA, which was comparable to that of the heterologous ELISA format that used the same mAb7G2. We also investigated the possible recognition mechanism of mAbs in terms of conformational and electronic aspects. The developed FPIA was applied to chicken to detect AMD residue, demonstrating a limit of detection (LOD) of 0.9 µg/kg with recoveries of 76.5–89.3% and coefficients of variation (CVs) below 14.5%. These results show that the proposed FPIA is an efficient, accurate, and convenient method for the rapid screening of AMD residues in chicken. Practical Application: The fluorescence polarization immunoassay (FPIA) was developed to determine and quantify amantadine (AMD) in chicken samples with high sensitivity. This homogeneous method avoids coating and washing steps and may provide high‐throughput AMD screening in chicken in 10 min with high accuracy and precision. FPIA can be used as a monitoring tool and contribute significantly to the rapid detection of AMD in chicken.